Contribution to the flora of Asian and European countries: new national and regional vascular plant records, 5. Issue 2 (2nd April 2016) - Nobis, Marcin; Nowak, Arkadiusz; Piwowarczyk, Renata; Ebel, Aleksandr L.; Király, Gergely; Kushunina, Maria; Sukhorukov, Alexander P.; Chernova, Olga D.; Kipriyanova, Laura M.; Paszko, Beata; Seregin, Alexey P.; Zalewska-Gałosz, Joanna; et al.
Abstract: The paper presents new records for 19 vascular plant species from 14 Eurasian countries. Two taxa ( Siphonostegia chinensis and Utricularia macrorhiza ) are reported from Russia, two ( Achnatherum botschantzevii and Stipa zalesskii ) from Kyrgyzstan, one ( Allium petraeum ) from Uzbekistan, three ( Crambe orientalis, Eleocharis mamillata and Geranium pratense subsp. sergievskajae ) from Kazakhstan, two ( Atriplex crassifolia and Petrosimonia brachyphylla ) from China, one ( Crambe orientalis ) from Tajikistan, one ( Stipa krylovii ) from India, one ( Agrostis lazica ) from Iraq, two ( Orobanche coerulescens and Orobanche zajaciorum ) from Armenia, one ( Phelipanche lavandulacea ) from Montenegro, one ( Panicum riparium ) from Bosnia and Herzegovina, Romania and Sweden, one ( Sporobolus vaginiflorus ) from Bosnia and Herzegovina and two ( Ranunculus penicillatus subsp. pseudofluitans and Scutellaria minor ) from Poland. Three of the taxa presented ( Crambe orientalis, Panicum riparium and Sporobolus vaginiflorus ) are regarded as alien to the studied areas, whereas the remaining 16 are native elements to the flora of the countries. For each species, synonyms, general distribution, habitat preferences, taxonomy with remarks on recognition and differentiation of the species from the most similar taxa occurring in a given country, as well as a list of recorded localities (often far from the previously known areas) are presented.